2020
DOI: 10.5195/jyd.2020.795
|View full text |Cite
|
Sign up to set email alerts
|

Camp Organizational Support for Creativity Among New And Returning Camp Counselors

Abstract: Creativity supports interest, imagination, empowerment, intrinsic motivation, and overall engagement. Satisfied employees, who are supported in their creativity, have increased performance, motivation, and commitment. Residential summer camp is a demanding 24-hour job in which camp counselors use creativity on a regular basis via lesson planning, teaching activities, resolving conflict, and living within close proximity to coworkers. The purpose of the current study was to explore organizational support for cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It is critical for camp leadership to acknowledge the difficulties of this study, including the effects of secondary trauma. To further prevent burnout, camp leaderships should engage staff in opportunities for creativity and innovation (Lynch et al, 2020) in managing secondary trauma. We encourage ongoing conversations on mental health at the leadership level, including during staff meetings and at camp conferences to allow for all stakeholders quo to contribute their ideas for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical for camp leadership to acknowledge the difficulties of this study, including the effects of secondary trauma. To further prevent burnout, camp leaderships should engage staff in opportunities for creativity and innovation (Lynch et al, 2020) in managing secondary trauma. We encourage ongoing conversations on mental health at the leadership level, including during staff meetings and at camp conferences to allow for all stakeholders quo to contribute their ideas for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…It is not only campers who look forward to camp; research examining summer camp staff retention suggests camp staff members are motivated to return to camp for a host of reasons, both personal and professional. For example, research has found camp to provide a space for staff—particularly emerging adults—to explore their interests, passions, teaching styles, and creative skills (Hall et al, 2020; Johnson et al, 2011; Lynch et al, 2020). Coupled with a desire to make a difference in the lives of campers, these learning opportunities cause many staff to find working at camp to be personally rewarding (Richmond et al, 2020).…”
Section: Introductionmentioning
confidence: 99%